2018
DOI: 10.3390/molecules23020466
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inhibitory Capacities of 6-, 8- and 10-Gingerols/Shogaols on the Canonical NLRP3 Inflammasome-Mediated IL-1β Secretion

Abstract: Endogenous noninfectious substances that mediate the nucleotide oligomerization domain (NOD)-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome activation and interleukin (IL)-1β secretion causes inappropriate sterile inflammation and is implicated in the pathogenesis of several chronic diseases, such as type 2 diabetes mellitus, gout, atherosclerosis and Alzheimer’s disease. Consequently, dietary phytochemicals exhibiting capacities to suppress canonical NLRP3 inflammasome-mediated IL-1β secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…In LPS-stimulated macrophages, 6-gingerol decreased iNOS and TNF-α expression by inhibiting NF-κB and PKC signaling [300]. In another study, 6-shogaol significantly inhibited the canonical NLRP3 inflammasome-mediated IL-1β secretion in THP-1 macrophages stimulated with LPS [301]. In a recent in vivo study, Wang et al demonstrated that administration of 6-gingerol to fat-fed apoE-deficient mice determines the reduction of atherosclerosis, expressed as decreased plaque formation and reduced levels of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) by a mechanism mediated in part by AMPK activation [302].…”
Section: Discussionmentioning
confidence: 94%
“…In LPS-stimulated macrophages, 6-gingerol decreased iNOS and TNF-α expression by inhibiting NF-κB and PKC signaling [300]. In another study, 6-shogaol significantly inhibited the canonical NLRP3 inflammasome-mediated IL-1β secretion in THP-1 macrophages stimulated with LPS [301]. In a recent in vivo study, Wang et al demonstrated that administration of 6-gingerol to fat-fed apoE-deficient mice determines the reduction of atherosclerosis, expressed as decreased plaque formation and reduced levels of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) by a mechanism mediated in part by AMPK activation [302].…”
Section: Discussionmentioning
confidence: 94%
“…So far, several factors have been demonstrated to lead to the activation of the NLRP3 inflammasome. For the initiation of the NLRP3 inflammasome, lipopolysaccharide (LPS) is widely considered to be a classic ligand for the activation of the TLR4 ( Chu et al, 2018 ; Ho and Chang, 2018 ). In addition, several factors have been shown to be effective to induce the second step of the NLRP3 inflammasome activation, including the adenosine triphosphate (ATP, triggering the intracellular K + efflux), PAMPs, DAMPs, silica, β-amyloid, autophagy deficiency as well as factors leading to the enhancement of mitochondrial Ca 2+ overload and so on ( Shao et al, 2017b ; Chen et al, 2018 ; Li et al, 2018b ; Meng et al, 2018 ; Zhao et al, 2018 ).…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…Additionally, the increase in the alkyl side chain length weakened the entry capacity in blood of gingerols and shogaols. The t 1/2 of shogaols were longer than gingerols indicating that shogaols had a relatively long residence time in the body and it may be the reason that shogaols exhibited higher biological activities than gingerols to a certain extent [18,20]. Abnormally, 6-gingerol is the most abundant in ginger, but the detected plasma concentration was not very high (the C max of 6-gingerol was 255.4 ± 44.7 μg/L), probably due to the major existing form of 6-gingerol in plasma is its glucuronide metabolites [26,27], which is consistent with the previous study [27].…”
Section: Resultsmentioning
confidence: 99%
“…The non-volatile compounds are gingerols, shogaols, paradols, and zingerone [14], sharing the same parent nucleus structure and are responsible for pharmacological functions in fresh ginger [15,16]. Previous studies demonstrated that gingerols and shogaols have diverse pharmacological activities, especially for 6-gingerol and 6-shogaol, have been proven to exhibit significant anti-hyperglycemic activity [17], antioxidant [18], analgesic [19], anti-inflammatory [20], anti-cancer [21], anti-arteriosclerosis [22], and lifespan-extending functions [23,24].…”
Section: Introductionmentioning
confidence: 99%